THE STATE OF ANIMAL WASTE RENDERING AND DISPOSING SYSTEM IN THE SUBJECTS OF THE RUSSIAN FEDERATION - A. V. Belchikhina; M. A. Shibaev; I. M. Klinovitskaya; A. K. Karaulov (Ветеринария сегодня)
Organizations of all forms of ownership engaged in the production, transportation, procurement and processing of animal products and raw materials, as well as backyards, produce a signifi cant amount of biological waste in the course of their activity. This waste is the source of environmental pollution, it contributes to the maintenance of infectious disease outbreaks and poses a real threat to public and livestock health. Facilities for biological waste rendering and disposal require constant monitoring and supervision, because the improper management of these facilities can lead to disease occurrence and spread with signifi cant environmental, economic and social implications. In order to objectively refl ect the real state of waste rendering and disposal facilities in the Subjects of the Russian Federation and to form a holistic view of the problem in the country, the analysis of data, collected from the veterinary executive authorities of the Subjects of the Russian Federation, were analyzed. Such parameters as quantity, form of ownership, veterinary and sanitary condition, location and availability of animal waste rendering and disposal facilities were considered as of 2018. The study revealed 20,808 animal waste rendering and disposal facilities registered in the country, the majority of them being represented by animal burial sites (including anthrax). In most cases, animal burial sites (including anthrax) do not meet veterinary and sanitary requirements and are unattended. The analysis reveals tension in the fi eld of animal waste management in the Russian Federation.